Entrepreneurial Subjective Ambivalence and Venture Idea Revision - Kiss, Andreea N.; Rothman, Naomi B.; Das, Willy; Hwang, Insung (Journal of Management, 2026)
We investigate the effects of entrepreneurial subjective ambivalence on a form of adaptive action: venture idea revision. Building on the affect-as-information perspective, we propose that entrepreneurial subjective ambivalence will increase venture idea revision by increasing information search behaviors. The results of a longitudinal, repeated-measures field study based on 175 entrepreneurs in a top incubator program demonstrate that when entrepreneurs experience higher subjective ambivalence (compared to lower ambivalence) in response to mentor feedback about their new ventures, they engage in higher levels of venture idea revision. We theorize and find that this increase in venture idea revision arises because subjective ambivalence is positively associated with more intense and broader information search behaviors. We discuss implications of our findings for research on affect in entrepreneurial decision-making, creative revision, and ambivalence in organizations, as well as for formal entrepreneurial mentoring programs.